Marketing 3.0 y su influencia en la imagen de marca de las entidades financieras de Trujillo - 2014. - Luján Velásquez, Jason Renzo (2014)
This document has been prepared to determine the influence of marketing 3.0 on the branding of financial institutions Trujillo. For they raised the following hypothesis where the use of marketing 3.0 has a positive influence on brand image entities Trujillo. The methodology used in this work will be by the Analytical method - Synthetic - deductive. Here we will interview people over 18 years in the district of Trujillo (315 400 inhabitants, INEI 2012) that applying our probabilistic sample we determine that we will be using the survey to 384 users between workers and clients of financial institutions in the Trujillo. Noting the emerging use of social media as a communication channel between corporations and consumers, is producing an impact on purchase intention which has not gone unnoticed by the organizations are adapting their marketing strategies and increased their presence on platforms like Facebook, Twitter and others. The lack of empirical studies that show the factors that can predict the intentions of participation and the need to measure the impact and benefits of such interaction in virtual communities created by organizations in these social networks have been the main reasons through the use of quantitative techniques such as surveys and qualitative direct observation, have promoted the study of social networks to find out how users influence the participation of these businesses in social networks. In studies performed in the course of this research, various financial firms have reflected the speed with which the market is growing and opportunities in the short, medium and long term are taking place in social media. Among the various benefits of a correct strategy and managing customer relationships are increased customer engagement with the brand with which they interact and the extraordinary nature of these platforms as marketing tools.